Investigation of boriding kinetics of AISI D2 steel. (July 2014) - Ortiz-Domínguez, M.; Keddam, M.; Elias-Espinosa, M.; Damián-Mejía, O.; Flores-Rentería, M. A.; Arenas-Flores, A.; Hernández-Ávila, J.
<x content-type="archive" xml:space="preserve">Abstract</x> A diffusion model was suggested to analyse the growth kinetics of Fe2B layers formed on AISI D2 steel by the pack-boriding process. It was used to estimate the boron diffusion coefficients of Fe2B in the temperature range of 1123–1273 K by applying the mass balance equation at the (Fe2B/substrate) interface. The proposed model was validated experimentally at 1253 K for a treatment time of 5 h by comparing the experimental Fe2B layer thickness with the predicted value. Furthermore, the pack-borided AISI D2 steel was characterised by optical microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray diffraction analysis. A contour diagram describing the evolution of Fe2B layer thickness as a function of the process variables was also proposed. In addition, the boron activation energy for AISI D2 steel was found to be equal to 201·50 kJ mol−1, on the basis of our experimental results.